The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1021/acsaem.1c02259
|View full text |Cite
|
Sign up to set email alerts
|

Growth and Photovoltaic Device Application of Cu2BaGe1–xSnxSe4 Films Prepared by Selenization of Sequentially Deposited Precursors

Abstract: Toward suppressing the formation of anti-site defects and related defect clusters in kesterite Cu 2 ZnSnS 4−x Se x (CZTS) absorber films, Cu 2 −II−IV−X 4 (II = Sr, Ba; IV = Ge, Sn; X = S, Se) compounds have recently been introduced. Cu 2 BaGe 1−x Sn x Se 4 (CBGTSe) is one of the materials that belongs to this chalcogenide family, with a tunable band gap (1.6 eV ≤ E g ≤ 1.9 eV, based on the x value) having been demonstrated for bulk samples. In this report, we demonstrate the deposition of CBGTSe films and repo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(17 citation statements)
references
References 53 publications
0
17
0
Order By: Relevance
“…It is noteworthy that such improvement with annealing has also been reported for other copper chalcogenidebased solar cells-that is, CZTS, [40][41][42] CBTSSe, [8] CBGSe, [10] and CBGTSe. [11] The improvement has been attributed to modification of heterojunction properties [40,41] and the passivation of grain boundaries by oxides (e.g., SnO x ). [8,42] J-V and EQE curves for the best-performing postannealed ACBGTSe solar cells are shown in Figure 6, with the corresponding solar cell performance parameters summarized in Table 1.…”
Section: Acbgtse Solar Cellsmentioning
confidence: 99%
“…It is noteworthy that such improvement with annealing has also been reported for other copper chalcogenidebased solar cells-that is, CZTS, [40][41][42] CBTSSe, [8] CBGSe, [10] and CBGTSe. [11] The improvement has been attributed to modification of heterojunction properties [40,41] and the passivation of grain boundaries by oxides (e.g., SnO x ). [8,42] J-V and EQE curves for the best-performing postannealed ACBGTSe solar cells are shown in Figure 6, with the corresponding solar cell performance parameters summarized in Table 1.…”
Section: Acbgtse Solar Cellsmentioning
confidence: 99%
“…CBGTSe films ( x = 0.5–0.6) have been prepared by selenizing Cu–Ba–Ge–Sn precursor multilayers that were sequentially deposited using vacuum-based techniques, including both sputtering (for Cu, Ge and Sn) and evaporation (for Ba). 137 Vacuum-deposition of related Cu 2 –II–IV–X 4 films ( i.e. , CBTS, 106,132,138 CBTSSe, 105,139,140 and CSTS 141 ) to yield functioning solar cells has only been demonstrated using the co-sputtering approach.…”
Section: Moving Beyond Cbtssementioning
confidence: 99%
“…, Ba). 142 Kim and Mitzi’s study 137 showed that such issues can be prevented using a high temperature vacuum pre-annealing step to partially homogenize the metallic precursor layer. The CBGTSe films exhibit a PL peak centered at 1.67 eV at room temperature, which is at a lower energy than for CBGSe (1.96 eV), reflecting an ∼0.3 eV bandgap reduction via partial substitution of Ge with Sn.…”
Section: Moving Beyond Cbtssementioning
confidence: 99%
See 2 more Smart Citations